Impact of Strongyloides stercoralis infection on complement activation in Type 2 diabetes mellitus: Insights from a clinical and anthelmintic intervention study. - Anuradha Rajamanickam; Bindu Dasan; Saravanan Munisankar; Sujatha Nott; Pradeep A Menon; Fayaz Ahamed Shaik; Ponnuraja Chinnaiyan; Thomas B Nutman; Subash Babu (Public Library of Science (PLoS), 2024)
Background Numerous studies indicate a potential protective role of helminths in diabetes mellitus (DM) progression. The complement system, vital for host defense, plays a crucial role in tissue homeostasis and immune surveillance. Dysregulated complement activation is implicated in diabetic complications. We aimed to investigate the influence of the helminth, Strongyloides stercoralis (Ss) on complement activation in individuals with type 2 DM (T2D). Methodology We assessed circulating levels of complement proteins (C1q, C2, C3, C4, C4b, C5, C5a, and MBL (Lectin)) and their regulatory components (Factor B, Factor D, Factor H, and Factor I) in individuals with T2D with (n = 60) or without concomitant Ss infection (n = 58). Additionally, we evaluated the impact of anthelmintic therapy on these parameters after 6 months in Ss-infected individuals (n = 60). Results Ss+DM+ individuals demonstrated reduced levels of complement proteins (C1q, C4b, MBL (Lectin), C3, C5a, and C3b/iC3b) and complement regulatory proteins (Factor B and Factor D) compared to Ss-DM+ individuals. Following anthelmintic therapy, there was a partial reversal of these levels in Ss+DM+ individuals. Conclusion Our findings indicate that Ss infection reduces complement activation, potentially mitigating inflammatory processes in individuals with T2D. The study underscores the complex interplay between helminth infections, complement regulation, and diabetes mellitus, offering insights into potential therapeutic avenues.